The effect of spirituality and health perception on screening behavior of people with and without a family history of cancer - Soylar, Pinar; Ozer, Ali (Springer Heidelberg, 2024)
Aim This study explored the role of health perceptions and spirituality on cancer screening participation among people with and without cancer history in first degree relatives (FDRs). Subject and methods A cross-sectional study was conducted in Elazig, Turkey, with 150 individuals (75 individuals without a family history of cancer and 75 individuals with a family history of cancer). Spirituality and health perception of participants were measured using the Perception of Health Scale and Spirituality Scale at Firat University Hospital. Univariate analysis (independent t-test/chi-square test) was applied first to identify the candidate independent variables. Then, multivariate logistic regression was used to examine the association between independent variables and participation in cancer screenings. Results People with cancer history in FDRs participated in more cancer screening such as mammography and colonoscopy than those without FDRs (p = 0.002 and p = 0.001, respectively). People with cancer history in FDRs participated have a better health perception than without FDRs (p = 0.001). Women (OR 3.694; 95% CI, 1.207-11.301; p = 0.022), health perception (OR 1.480; 95% CI, 1.290-1.697; p = 0.001), and spirituality (OR 1.074; 95% CI, 1.028-1.122; p = 0.001), were positively associated with the likelihood of participating in cancer screening. Conclusion Our study emphasized that spirituality and health perception promote the participation in cancer screening. Future studies with large sample size are suggested to examine cancer screening behaviors for Turkish at-risk populations due to family history.
Keywords: Cancer screening; first degree relatives; spirituality; health perception